Response of the temperate scleractinian coral Cladocora caespitosa to high temperature and long-term nutrient enrichment - Hadjioannou, Louis (Sci Rep, 2019)
Anthropogenic nutrient enrichment and increased seawater temperatures are responsible for coral reef decline. In particular, they disrupt the relationship between corals and their dinoflagellate symbionts (bleaching). However, some coral species can afford either high temperatures or nutrient enrichment and their study can bring new insights into how corals acclimate or adapt to stressors. Here, we focused on the role of the nutrient history in influencing the response of the Mediterranean scleractinian coral Cladocora caespitosa to thermal stress. Colonies living naturally in nutrient-poor (<0.5 µM nitrogen, <0.2 µM phosphorus, LN) and nutrient-rich (ca. 10–20 µM nitrogen, 0.4 µM phosphorus, HN) locations were sampled, maintained under the right nutrient conditions, and exposed to a temperature increase from 17 °C to 24 °C and 29 °C. While both HN and LN colonies decreased their concentrations of symbionts and/or photosynthetic pigments, HN colonies were able to maintain significant higher rates of net and gross photosynthesis at 24 °C compared to LN colonies. In addition, while there was no change in protein concentration in HN corals during the experiment, proteins continuously decreased in LN corals with increased temperature. These results are important in that they show that nutrient history can influence the response of scleractinian corals to thermal stress. Further investigations of under-studied coral groups are thus required in the future to understand the processes leading to coral resistance to environmental perturbations.